ІГРОВА КОНЦЕПЦІЯ КУЛЬТУРИ Й. ХЬОЙЗІНГИ - Білик, Я. М. (The Journal of V. N. Karazin Kharkiv National University. Series "Theory of Culture and Philosophy of Science")
Метою цієї статті є аналіз того внеску в концептуальну еволюцію лудологічних понять, який пов’язаний з іменем Й. Хьойзінги. Визначається історичне місце його ігрової концепції культури, аналізується дефініція ігрового феномену та його ідеї щодо значення окремих культурних форм гри. Ключові слова: ігровий феномен, культурні форми гри, Й. Хьойзінга. Билык Я.М. ИГРОВАЯ КОНЦЕПЦИЯ КУЛЬТУРЫ Й. ХЬОЙЗИНГИ. Целью данной статьи является анализ того вклада в концептуальную эволюцию лудологических понятий, который связан с именем Й. Хьойзинги. Определяется историческое место его игровой концепции культуры, анализируется дефиниция игрового феномена и его идеи о значении некоторых культурных форм игры. Ключевые слова: игровой феномен, культурные формы игры, Й. Хьойзинга. Y. Bilyk. J. HUIZINGA GAME CONCEPTION OF CULTURE. The aim of the given article is the analysis of that contribution into conceptual evolution of ludological notions which is connected with the name of J. Huizinga. The historical place of his game conception of culture is defined, the definition of game phenomenon and his idea about the meaning of some cultural forms of the game is analysed. Key words: game phenomenon, cultural forms of game, J. Huizinga.